2014
DOI: 10.1080/02646838.2014.956301
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the parent–baby bond in men and women 15 months after birth

Abstract: Objective: To prospectively examine the impact of parental mental health (PTSD, depression and anxiety), the couple's relationship quality and the infant temperament on the parent-baby bond in first-time mothers and fathers. Background: Evidence suggests that poor parental mental health, difficult infant temperament and/or lower quality of the couple's relationship may impede the parent-baby bond. However, little research has included both parents or followed these measures across time. Methods: 75 women and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 62 publications
5
40
0
1
Order By: Relevance
“…However, four studies did not report this figure (Parfitt, Ayers, Pike, Jessop, & Ford, 2014;Pierrehumbert, Nicole, Muller-Nix, Forcada-Guex, & Ansermet, 2003;Seng, et al, 2013;Yehuda, et al, 2005), which means that conclusions should be drawn cautiously.…”
Section: Study Characteristicsmentioning
confidence: 98%
“…However, four studies did not report this figure (Parfitt, Ayers, Pike, Jessop, & Ford, 2014;Pierrehumbert, Nicole, Muller-Nix, Forcada-Guex, & Ansermet, 2003;Seng, et al, 2013;Yehuda, et al, 2005), which means that conclusions should be drawn cautiously.…”
Section: Study Characteristicsmentioning
confidence: 98%
“…Some researchers propose that bonding difficulties develop secondary to an untreated primary mother’s postpartum depression, whereas others suggest that these can also occur in women who have not suffered from maternal depression ( 7 ). Regarding fathers, one small study (n = 66) showed that affective symptoms at 3 months postpartum was not associated with father-infant bonding at 3 months postpartum but predicted father-infant bonding at 15 months postpartum ( 10 ). However, more evidence in a larger sample is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien el hombre no experimenta los cambios fidios de llanto prolongado y dificultades en el sueño de sus hijos pequeños 6 , existen mayores dificultades en la interacción [22][23][24] , los lactantes presentarían mayores dificultades en la conducta alimentaria 19 y además existe un mayor riesgo de desarrollar un estilo de apego inseguro 25 . En el mediano plazo, los hijos de padres con DPP tienden a presentar un aumento tanto en la frecuencia de alteraciones del comportamiento, tales como problemas de conducta o hiperactividad 25 , como en los problemas emocionales 26 .…”
Section: Introductionunclassified